2015
DOI: 10.1097/pcc.0000000000000362
|View full text |Cite
|
Sign up to set email alerts
|

Functional Recovery Following Critical Illness in Children

Abstract: Objective To determine the feasibility of conducting a longitudinal prospective study to evaluate functional recovery and predictors of impaired functional recovery in critically ill children. Design Prospective pilot study. Setting Single center Pediatric Intensive Care Unit (PICU) at McMaster Children’s Hospital, Hamilton, Canada. Patients Children aged 12 months to 17 years, with at least one organ dysfunction, limited mobility or bed-rest during the first 48 hours of PICU admission, and a minimum 48 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 35 publications
(44 reference statements)
1
45
0
5
Order By: Relevance
“…Chong et al showed that 30% of pediatric ICU patients develop weakness in the ICU [25], and older children have been found to be more affected by muscle wasting than younger ones [26]. Given that the average age of the current study population was relatively young, at a mean of 10 years, the results of this study would be expected to be less affected by the effects of a wide age range.…”
Section: Discussionmentioning
confidence: 85%
“…Chong et al showed that 30% of pediatric ICU patients develop weakness in the ICU [25], and older children have been found to be more affected by muscle wasting than younger ones [26]. Given that the average age of the current study population was relatively young, at a mean of 10 years, the results of this study would be expected to be less affected by the effects of a wide age range.…”
Section: Discussionmentioning
confidence: 85%
“…As previously described, a recent pediatric pilot study predicted ICU-AW in 30% of patients and confirmed ICU-AW in 6.7% of at-risk patients [23]. Diagnosis of ICU-AW in children is hindered by the lack of a suitable diagnostic tool [23].…”
Section: Pediatric Mobilizationmentioning
confidence: 91%
“…In a recent pediatric pilot study, ICU-AW was confirmed in 6.7% of "at-risk" patients and suspected in 30% [23]. Intensive care unit-acquired weakness is age dependent, with 0.7% of very young children and 5.1% of older children exhibiting muscle weakness [23,24].…”
Section: Consequences Of Immobility In the Critically Illmentioning
confidence: 99%
See 1 more Smart Citation
“…27 The reported incidence of PICU-acquired weakness from prospective studies varies from 1.7 to 30%. 28,29 Its significance and impact on functional recovery and long-term outcomes remains unclear, and is a growing area of interest in critically ill children. 30 …”
Section: The Post–intensive Care Syndrome In Childrenmentioning
confidence: 99%